RETRACTED: Project methods for improving the main parameters of the implementation of projects and programs of socio-demographic development in the regions of the Central Chernozem Economic Region - Khripkova Dianna; Khripkov Kirill; Vangorodskaya Svetlana; Gaidukova Galina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001